Pengembangan Kit Optik sebagai Media Praktikum Cahaya dan Optik untuk Meningkatkan Keterampilan Proses Sains - Ady Tri Wibowo; Akhmad Marzuqi (Jurnal Edutrained : Jurnal Pendidikan dan Pelatihan, 2022)
This study aims to develop an optical tool kit and teaching aid toward the improvement of students' science process skills. The methods that are used are research and development methods of 4-dimensional models. The research instrument included tests, questionnaires, and observation sheets. The optical tool kit has a portable design and is simpler than the optical tool kit in a school laboratory. The result of this study showed that the improvements of science process skills, as indicated by the normalized gain value of 0,33 that was included insufficient criteria. The practical evaluation of the optical kit was performed by expert validators and result scores were obtained by 85% for the tools and 93.7% for the manual. The highest indicator of science process skills in observing, while the lowest indicator of science process skills was data interpretation. The questionnaire toward optical tool kit teaching aids obtained a score of 85.7% for an optical tool kit and 82.4% for manual.